2011
DOI: 10.1186/1477-7819-9-161
|View full text |Cite
|
Sign up to set email alerts
|

A patient with spontaneous rupture of the esophagus and concomitant gastric cancer whose life was saved: case of report and review of the literature in Japan

Abstract: A 71-year-old man suddenly developed abdominal pain and vomiting on drinking soda after a meal, and visited a physician. Cervical subcutaneous and mediastinal emphysemas were observed on CT, and the patient was transferred to the emergency medical center of our hospital on the same day. Esophagography was performed at our department. A ruptured region was identified on the left side of the lower thoracic esophagus, and surgery was emergently performed employing sequential left thoracoabdominal incision. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Malignant GOO can lead to perforation of the stomach or the esophagus. There have been case reports of esophageal perforation secondary to malignant GOO, and the location of all the tumors was found to be in the pre-pyloric region [8][9][10]. There have been case reports of gastric perforation due to gastric obstruction [11].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant GOO can lead to perforation of the stomach or the esophagus. There have been case reports of esophageal perforation secondary to malignant GOO, and the location of all the tumors was found to be in the pre-pyloric region [8][9][10]. There have been case reports of gastric perforation due to gastric obstruction [11].…”
Section: Discussionmentioning
confidence: 99%
“…This is the tenth reported case of esophageal perforation secondary to gastric outlet obstruction (GOO) from gastric cancer and the first to be temporized by esophageal and pyloric stenting with transluminal perforation management. Previously, Matsuhashi and colleagues [4] published the first English language case report of esophageal perforation secondary to malignant GOO. Their 2011 literature review identified five other similar cases.…”
Section: Discussionmentioning
confidence: 99%
“…[1314] Tissues such as the intercostal muscles, pleura, omentum and pericardium pedicle flaps may be used to strengthen the repair line in the perforated area, but discussions about their efficacy remain. [1516] The sternothyroid and sternocleidomastoid muscles may also be used in cervical oesophagus perforation. [17]…”
Section: Discussionmentioning
confidence: 99%